2008
DOI: 10.1126/science.1155847
|View full text |Cite
|
Sign up to set email alerts
|

Role of C. elegans TAT-1 Protein in Maintaining Plasma Membrane Phosphatidylserine Asymmetry

Abstract: The asymmetrical distribution of phospholipids on the plasma membrane is critical for maintaining cell integrity and physiology and for regulating intracellular signaling and important cellular events such as clearance of apoptotic cells. How phospholipid asymmetry is established and maintained is not fully understood. We report that the Caenorhabditis elegans P-type adenosine triphosphatase homolog, TAT-1, is critical for maintaining cell surface asymmetry of phosphatidylserine (PS). In animals deficient in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
137
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 24 publications
8
137
1
1
Order By: Relevance
“…In yeast, the major phenotype associated with loss of P4-ATPase function is abnormal transport vesicle budding from the transgolgi network (19,33,34). Similar defects in cargo sorting have been observed in Caenorhabditis elegans Tat-1 mutants (35), and other C. elegans P4-ATPase mutants are defective for phagocytosis of dead cells and regulation of ectosome production (35)(36)(37)(38). Proper lipid localization may be required for vesicle docking or receptor recycling leading to reduced receptor levels in the cilia.…”
Section: Discussionmentioning
confidence: 89%
“…In yeast, the major phenotype associated with loss of P4-ATPase function is abnormal transport vesicle budding from the transgolgi network (19,33,34). Similar defects in cargo sorting have been observed in Caenorhabditis elegans Tat-1 mutants (35), and other C. elegans P4-ATPase mutants are defective for phagocytosis of dead cells and regulation of ectosome production (35)(36)(37)(38). Proper lipid localization may be required for vesicle docking or receptor recycling leading to reduced receptor levels in the cilia.…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of the loss of at least 1 touch-receptor neuron (abbreviated 'loss of touch-receptor neurons') in these btbd-10 mutants was comparable to the frequency of the loss of touch-receptor neurons in tat-1(tm1034);bzIs8 worms, a previously reported line that exhibits substantial loss of touch-receptor neurons (Figure 2c). 18 Importantly, the loss of touch-receptor neurons in btbd-10 mutants was rescued by the introduction of the 8.07-kb btbd-10( þ ) transgene (Figure 2c and Supplementary Figure S2) or by the introduction of the cDNA encoding N-terminally mCherry-tagged human BTBD10 under the control of the worm btbd-10 gene promoter (P btbdÀ10 ::mCherry:: hBTBD10) (Figure 2c). Loss of touch-receptor neurons was also suppressed by the disruption of the ced-3 gene (Figure 2c), an executioner of the caspase cascade in C. elegans.…”
Section: Resultsmentioning
confidence: 99%
“…Whether neutrophils exposing PS and generating lyso-PS in vivo are truly "eaten alive" or are beginning to undergo early apoptosis is at this point unclear and there is likely a continuum between PS exposure during activation and the appearance of other markers signifying cell death (59). We and others have previously published that PS exposure occurs on activated cells including neutrophils (53,54), and that PS on living cells can act as an "eat me" signal in mammalian systems (14) and possibly in Caenorhabditis elegans (60). In addition, this possibility may also explain the findings of Lagasse and Weissman (52) who demonstrated that activated neutrophils overexpressing Bcl-2, which were devoid of classic features of apoptosis (e.g.…”
Section: Discussionmentioning
confidence: 99%